INVESTIGATING THE ROLE OF B-CELL ACTIVATING FACTOR (BAFF), GALECTIN-9, AND CD73 IN THE PATHOGENESIS OF VITILIGO: A CORRELATIVE STUDY WITH BIOCHEMICAL FACTORS - AL-Ukaily, Hussein Ali Mohammed (Journal of Medical Genetics and Clinical Biology, 2025)
Objective: To investigate the involvement of immune-regulatory molecules—B-cell Activating Factor (BAFF), Galectin-9, and CD73—in the pathogenesis of vitiligo. Methods: A case-control study involving 50 patients with active vitiligo and 50 healthy controls. Peripheral blood and skin biopsy samples were collected to measure the concentrations of BAFF, Galectin-9, and CD73. Statistical analysis was conducted to evaluate differences and correlations between these markers. Results: The results showed that the levels of B-cell Activating Factor (BAFF) were significantly higher in vitiligo patients (150.64 ng/mL) compared to healthy controls (85.16 ng/mL). Similarly, Galectin-9 concentrations were elevated in patients (203.02 ng/mL) relative to controls (149.68 ng/mL). In contrast, CD73 levels were lower in vitiligo patients (49.66 ng/mL) compared to healthy controls (79.37 ng/mL), although this difference was not statistically significant. Correlation analysis revealed a positive association between BAFF and Galectin-9, while CD73 exhibited a negative correlation with both BAFF and Galectin-9. Novelty: The study identifies BAFF and Galectin-9 as potential biomarkers for vitiligo severity and suggests CD73 as a modulator of immune responses. This adds new insights into the immunopathology of vitiligo and highlights potential therapeutic targets